Penggunaan Rapid Application Development dalam Rancang Bangun Program Simpan Pinjam pada Koperasi - Hidayati, Nur (Universitas Nusantara PGRI Kediri, 2018)
Cooperatives in Indonesia over the past four years have been very positive with an average of 2.5 percent of active cooperative growth. Based on government data up to July 5, 2017, cooperatives in Indonesia have 152,282 units of cooperatives and 26.8 million cooperative members. With the development of it, it is necessary also in the use of information systems in data processing. One type of cooperative is a savings and loan cooperative, and many cooperatives perform conventional data processing. It can cause problems like old search data, inaccurate borrowing and inaccurate reports. Therefore, the need for application programs that are applied, by creating a design program that is able to provide information in the process of storing information produced quickly, timely and accurate. Using the method of rapid application development (RAD), became one of the options to assist in the design program of saving and loan cooperatives. With the implementation of application programs on savings and loan cooperatives, it can be done existing solutions in data processing cooperative.